2014
DOI: 10.1007/s13277-014-2439-2
|View full text |Cite
|
Sign up to set email alerts
|

Novel methodologies in analysis of small molecule biomarkers and living cells

Abstract: Enzyme-linked immuno-sorbent assay (ELISA) is widely used for biomarker detection. A good biomarker can distinguish patients from healthy or benign diseases. However, the ELISA method is not suitable for small molecule or trace substance detection. Along with the development of new technologies, an increasing level of biomaterials, especially small molecules, will be identified as novel biomarkers. Quantitative immuno-PCR, chromatography-mass spectrometry, and nucleic acid aptamer are emerging methodologies fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…GC-MS is widely applied in metabolomics study, which provide a rapid, qualitative and quantitative analyses with the ability to identify small molecule metabolites [29, 30]. GC can separate volatile and thermal stable compounds, then the compounds are eluted and detected by MS. MS is operated by ion formation, separation and detection of ions according to mass-to-charge (m/z) ratio.…”
Section: Introductionmentioning
confidence: 99%
“…GC-MS is widely applied in metabolomics study, which provide a rapid, qualitative and quantitative analyses with the ability to identify small molecule metabolites [29, 30]. GC can separate volatile and thermal stable compounds, then the compounds are eluted and detected by MS. MS is operated by ion formation, separation and detection of ions according to mass-to-charge (m/z) ratio.…”
Section: Introductionmentioning
confidence: 99%
“…118 A microfluidic droplet system has also been developed for highthroughput screening of chemical libraries for discovery of smallmolecule inhibitors with a high-resolution dose-response relationship. 123,124 This study identified numerous inhibitors and indicated a most potent candidate, cefsulodin sodium, exhibiting an half maximal inhibitory concentration (IC50) of 27 ± 0.83 μM.…”
Section: Metabolites and Small-molecule Inhibitors As Affinity Reagentsmentioning
confidence: 99%
“…In DNA, biotin or avidin will link to a DNA fragment. Additionally, this assay can be classified in direct quantitative immuno-PCR, competitive quantitative immuno-PCR, and sandwich quantitative immuno-PCR (Singer et al 2009;Deng et al 2011;Chen et al 2014).…”
Section: Immunoassay System For Immuno-pcrmentioning
confidence: 99%
“…The qiPCR is used for quantification of proteins (Lind & Kubista 2005;Janssen et al 2013), and it was first described by Sims et al (2000). This quantitative system combines the advantages of immunoassays (flexibility and robustness) with the exponential signal amplification power and larger dynamic range of PCR, compared to ELISA (Table 1) (Lind & Kubista 2005;Niemeyer et al 2007;Chen et al 2014). It can be carried out by a gel electrophoresis or qPCR.…”
Section: Quantitative Real-time Immuno-pcr (Qipcr)mentioning
confidence: 99%
See 1 more Smart Citation